Characterisation of Bioglass based foams developed via replication of natural marine sponges - Boccardi, Elena; Philippart, Anahi; Juhasz-Bortuzzo, Judith Agnes; Novajra, G.; Vitale-Brovarone, C.; Boccaccini, Aldo R. (Advances in Applied Ceramics, 2015)
A comparative characterisation of Bioglass based scaffolds for bone tissue engineering applications developed via a replication technique of natural marine sponges as sacrificial template is presented, focusing on their architecture and mechanical properties. The use of these sponges presents several advantages, including the possibility of attaining higher mechanical properties than those scaffolds made by foam replica method (up to 4 MPa) due to a decrease in porosity (68-76%) without affecting the pore interconnectivity (higher than 99%). The obtained pore structure possesses not only pores with a diameter in the range 150-500 mu m, necessary to induce bone ingrowth, but also pores in the range of 0-200 mu m, which are requested for complete integration of the scaffold and for neovascularisation. In this way, it is possible to combine the main properties that a three-dimensional scaffold should have for bone regeneration: interconnected and high porosity, adequate mechanical properties and bioactivity.
Keywords: Natural marine sponges; Bioglass; Replication technique